2018
DOI: 10.1016/j.molcel.2018.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Landscape of Human Folliculogenesis Reveals Oocyte and Granulosa Cell Interactions

Abstract: Highlights d RNA-seq of oocytes and granulosa cells mapped transcriptome and signature genes d KEGG/GSEA analysis uncovered pathways involved in primordial follicle activation d Oocyte-granulosa cell interactions exhibit stage-and species-specific patterns d RNA-seq analysis identified candidate secretory biomarkers of ovarian reserve

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
330
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 314 publications
(364 citation statements)
references
References 54 publications
17
330
0
Order By: Relevance
“…D, Relative quantification of the mean fluorescence intensity of AP2 in oocytes. Data are shown as the mean ± SEM, and different letters (a, b) represent a significant difference (P < .05) data in the existing databases (GSE107746, GSE36552), 42,43 the transcriptional expression levels of the marker genes in this study were shown to have dropped markedly in mature oocytes.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…D, Relative quantification of the mean fluorescence intensity of AP2 in oocytes. Data are shown as the mean ± SEM, and different letters (a, b) represent a significant difference (P < .05) data in the existing databases (GSE107746, GSE36552), 42,43 the transcriptional expression levels of the marker genes in this study were shown to have dropped markedly in mature oocytes.…”
Section: Discussionmentioning
confidence: 62%
“…The lack of statistical significance might be attributed to transcriptional repression because as much as half of the mRNA undergoes degradation or deadenylation during meiotic maturation . By looking up the single‐cell RNA‐seq data in the existing databases (GSE107746, GSE36552), the transcriptional expression levels of the marker genes in this study were shown to have dropped markedly in mature oocytes.…”
Section: Discussionmentioning
confidence: 78%
“…The canonical correlation analysis (CCA) of the expressed genes in all cell types at each developmental stage, is reported in Figures S1D and S1E. The top genes driving canonical correlation 1 (CC1) and 2 (CC2) include key genes such as Smc1b , Sycp1 , Syce2 and Sycp3 involved in germ cell meiosis (Bolcun-Filas, Costa et al, 2007, Garcia-Cruz, Brieno et al, 2010), Dazl and Xist driving germ cell transcription (Chen, Welling et al, 2014, Sado & Sakaguchi, 2013), and Sox4 and Wnt6 widely expressed in folliculogenesis (Harwood, Cross et al, 2008, Zhang, Yan et al, 2018, Zhao, Arsenault et al, 2017) (Figure S1F). A heatmap of the top ten marker genes for all six cell types is displayed in Figure S1G (Supplemental Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Presumably, identification of the decreased and stable RNA in this process could add understanding to the molecular regulation of oocyte development and quality control. Several RNA-seq readouts have been used to represent cross-stage differences such as FPKM (Fragments Per Kilobase Million) and RPM (Transcripts Per Kilobase Million) which are normalized by gene length and library size [10,14]. However, this library-size based quantification indicated as many genes with increased abundance as with decreased abundance which is difficult to explain biologically in the absence of transcription during oocyte maturation.…”
Section: External and Internal Normalization For Cross-stage Comparisonmentioning
confidence: 99%
“…Poly(A) RNA was isolated by oligo (dT) beads, reverse transcribed, amplified and purified [21]. Individual samples were tested for different amplification cycles (10,14,18), and different fractions of oocytes (1/8, 1/4, 1/2) were amplified for 18 cycles. After purification, cDNAs were evaluated by Bioanalyzer 2100 (Agilent).…”
Section: Rna-seq Library Preparation Of Intact and Fractions Of Mousementioning
confidence: 99%